Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline Pada Pembelajaran Ipa Kelas IV SDN 10 Mowila - Jingga Septiari; Ridwan Ardi; Ashari Usman (Prodi PGSD Unsultra, 2025)
The research carried out is included in the Research and Development (R&D) type of research using the modified Borg and Gall development model. The stages in this development research are research and data collection, planning, product development, initial field testing, initial product revision, main field testing and second product revision. The research subjects were 32 class IV students at SDN 10 Mowila. Research data collection techniques include observation, interviews, questionnaires, tests and documentation. Using types of primary data and secondary data. The research data analysis stage uses qualitative and quantitative data analysis techniques. The qualitative data analysis technique uses the Miles and Hubberman analysis model. Quantitative data analysis techniques include using the one group pretest posttest design average calculation model and average percentage calculation using a Likert scale reference. The results of the development research show that: (1) The results of media products that were validated obtained a design validation percentage of 91% in the very good category, material validation was 91% in the very good category, both of which show that the media is very valid and very suitable for use. (2) The level of media attractiveness was obtained through the results of student responses with a percentage of 87.6% in the interesting category. (3) The level of media effectiveness was obtained through pretest results of 62.18 and posttest results of 93.75. The difference in scores between the two shows that the application of media improves the results and learning of class IV students at SDN 10 Mowila